Insulin and IGF1 enhance IL-17-induced chemokine expression through a GSK3B-dependent mechanism: a new target for melatonin's anti-inflammatory action - Ge, Dongxia (2013)
Obesity is a chronic inflammation with increased serum levels of insulin, insulin-like growth factor 1 (IGF1), and interleukin-17 (IL-17). The objective of this study was to test a hypothesis that insulin and IGF1 enhance IL-17-induced expression of inflammatory chemokines/cytokines through a glycogen synthase kinase 3β (GSK3B)-dependent mechanism, which can be inhibited by melatonin. We found that insulin/IGF1 and lithium chloride enhanced IL-17-induced expression of C-X-C motif ligand 1 (Cxcl1) and C-C motif ligand 20 (Ccl20) in the Gsk3b(+/+) but not Gsk3b(−/−) mouse embryonic fibroblast (MEF) cells. IL-17 induced higher levels of Cxcl1 and Ccl20 in the Gsk3b(−/−) MEF cells, compared to the Gsk3b(+/+) MEF cells. Insulin and IGF1 activated Akt to phosphorylate GSK3B at serine 9, thus inhibiting GSK3B activity. Melatonin inhibited Akt activation, thus decreasing P-GSK3B at serine 9 (i.e., increasing GSK3B activity) and subsequently inhibiting expression of Cxcl1 and Ccl20 that was induced either by IL-17 alone or by a combination of insulin and IL-17. Melatonin's inhibitory effects were only observed in the Gsk3b(+/+) but not Gsk3b(−/−) MEF cells. Melatonin also inhibited expression of Cxcl1, Ccl20 and Il-6 that was induced by a combination of insulin and IL-17 in the mouse prostatic tissues. Further, nighttime human blood, which contained high physiologic levels of melatonin, decreased expression of Cxcl1, Ccl20 and Il-6 in the PC3 human prostate cancer xenograft tumors. Our data support our hypothesis and suggest that melatonin may be used to dampen IL-17-mediated inflammation that is enhanced by the increased levels of insulin and IGF1 in obesity.